2018
DOI: 10.3346/jkms.2018.33.e296
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Rates and Outcomes of HIV-Infected Women in Korea

Abstract: BackgroundAntepartum, intrapartum, and postpartum preventive measures with antiretroviral drugs, appropriate delivery methods, and discouraging breastfeeding significantly decrease the risk of mother-to-child transmission of human immunodeficiency virus (HIV) infection. Herein, we investigated the pregnancy outcomes in HIV-infected Korean women.MethodsWe retrospectively reviewed medical records of childbearing-age HIV-infected women between January 2005 and June 2017 at four tertiary care hospitals in Korea.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…This finding is higher than that of studies conducted in London (13/1000 person-years) [ 25 ], Korea (3.57/100 person-years) [ 26 ], Canada (2.91/100 person-years) [ 27 ], Eight west African countries (2.9/100 person-years), Burkina Faso (5/100 person-years) [ 28 ], and studies from Ethiopia: Addis Ababa (6.5/100 person-years) [ 29 ], and Debre Markos (4.92/100 person-years) [ 9 ]. This difference may be due to differences in; inclusion and exclusion criteria, the size of records reviewed, the study period, and difference in baseline exposure to ART.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is higher than that of studies conducted in London (13/1000 person-years) [ 25 ], Korea (3.57/100 person-years) [ 26 ], Canada (2.91/100 person-years) [ 27 ], Eight west African countries (2.9/100 person-years), Burkina Faso (5/100 person-years) [ 28 ], and studies from Ethiopia: Addis Ababa (6.5/100 person-years) [ 29 ], and Debre Markos (4.92/100 person-years) [ 9 ]. This difference may be due to differences in; inclusion and exclusion criteria, the size of records reviewed, the study period, and difference in baseline exposure to ART.…”
Section: Discussioncontrasting
confidence: 57%
“…Studies conducted from 1996 to 2016 4 , 6 , 18 , 19 , 20 , 21 reported pregnancy incidence ranging from 2.9 per 100 person-years 19 to 10.1/100 person-years 21 . Contrary to our findings, Haddad et al 6 , in a study conducted in 9 U.S. centers, reported a non-significant increase in pregnancy incidence in WLWHA and a significant increase in live births (from 2.85 to 7.27/100 person-years) in the periods 1994-1997 to 2006-2012, with similar values in WLWHA and in women not living with HIV/AIDS (WNLWHA) in more recent periods.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) provided and updated the recommendations on the regimens of antiretrovirals (ARVs) for pregnant women infected with HIV [ 30 – 32 ]. Additionally, some East Asia countries launched the prevention of mother-to-child transmission for HIV program and spread more knowledge of HIV transmission means from mother to child among women [ 33 , 34 ]. The predicted incidence of HIV in post-neonatal population showed a decreased trend in East Asia, except North Korea and South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…This maybe because the improved prevention, screening, and treatment strategies including ART for HIV [ 40 , 41 ]. Early HIV screening tests, avoid breastfeeding, and health care were provided in post-neonatal population with HIV, which might also help decrease the mortality of these patients [ 33 ]. In general, the incidence of HIV with XDR-TB in South Korea, North Korea, Mongolia, and Taiwan was increased during 2000–2019.…”
Section: Discussionmentioning
confidence: 99%